2023
DOI: 10.1002/yea.3903
|View full text |Cite
|
Sign up to set email alerts
|

Yeasts from tropical forests: Biodiversity, ecological interactions, and as sources of bioinnovation

Carlos A. Rosa,
Marc‐André Lachance,
Savitree Limtong
et al.

Abstract: Tropical rainforests and related biomes are found in Asia, Australia, Africa, Central and South America, Mexico, and many Pacific Islands. These biomes encompass less than 20% of Earth's terrestrial area, may contain about 50% of the planet's biodiversity, and are endangered regions vulnerable to deforestation. Tropical rainforests have a great diversity of substrates that can be colonized by yeasts. These unicellular fungi contribute to the recycling of organic matter, may serve as a food source for other org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 222 publications
0
5
0
Order By: Relevance
“…Tropical rainforests and other species-rich biomes can be found in Asia, Australia, Africa, Central and South America, Mexico, and many Paci c Islands. These biomes cover less than 20% of the Earth's land area but may contain up to 50% of the planet's biodiversity (Dinerstein et (Rosa et al, 2023). As these biomes are under threat due to deforestation (Hoang and Kanemoto, 2021) and environmental changes, it is important to catalog their microbial biodiversity before it is lost.…”
Section: Untargeted Yeast Bioprospecting Uncovers Isolates Of Potenti...mentioning
confidence: 99%
See 2 more Smart Citations
“…Tropical rainforests and other species-rich biomes can be found in Asia, Australia, Africa, Central and South America, Mexico, and many Paci c Islands. These biomes cover less than 20% of the Earth's land area but may contain up to 50% of the planet's biodiversity (Dinerstein et (Rosa et al, 2023). As these biomes are under threat due to deforestation (Hoang and Kanemoto, 2021) and environmental changes, it is important to catalog their microbial biodiversity before it is lost.…”
Section: Untargeted Yeast Bioprospecting Uncovers Isolates Of Potenti...mentioning
confidence: 99%
“…Whereas the yeast biodiversity of North America, Europe, and parts of Asia is somewhat well mapped, plenty of niches and geographical locations in the global south remain only super cially explored. These include biodiversity hotspots in tropical Africa and South America that likely hold many new yeast species and lineages with ecologically or industrially interesting traits (Boekhout et al, 2022;Rosa et al, 2023) Novel yeast strains and species can be found through bioprospecting -the systematic and organized search for useful products derived from bioresources (Hosseini et al, 2022). Untargeted bioprospecting aims to collect every microbe that grows on non-selective plates in the laboratory, while targeted bioprospecting collects microbes that grow well in a select environment, often of industrial interest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Species of the genus Starmerella exhibit unusual metabolic traits, such as fructophily and the production of sophorolipids [8]. Most species of the genus have been isolated from bees and substrates visited by these insects, indicating an ecological relationship between the yeasts and the insects [9][10][11][12][13][14]. Associations between stingless bees or honeybees and species of the genus Starmerella have been reported in recent works.…”
Section: Introductionmentioning
confidence: 99%
“…Many places and ecosystems remain unexplored despite geographical assessments of yeast biodiversity spanning various regions 11 . Large biomes such as tropical rainforests, montane, and sub-montane ecosystems have been understudied 12 .…”
Section: Introductionmentioning
confidence: 99%